2015
DOI: 10.1097/aog.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphism–Microarray Ploidy Analysis of Paraffin-Embedded Products of Conception in Recurrent Pregnancy Loss Evaluations

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…The search identified 630 articles, 29 of which were full-text reviewed and 20 of those were finally included in the meta-analysis 9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Nine studies were excluded either because reported data could not be extracted, or identification of the gestational age or indication for sampling for each case was not provided (if late pregnancy losses or other indications for CMA were included, respectively), or if only morphologically abnormal embryos were included or could not be identified (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search identified 630 articles, 29 of which were full-text reviewed and 20 of those were finally included in the meta-analysis 9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Nine studies were excluded either because reported data could not be extracted, or identification of the gestational age or indication for sampling for each case was not provided (if late pregnancy losses or other indications for CMA were included, respectively), or if only morphologically abnormal embryos were included or could not be identified (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 23 studies included in the meta-analysis are outlined in Table 1. Ten studies included only first-trimester pregnancy losses 9,20,22,23,25,30,35,37,38,40 and 13 included losses under 20 weeks 19,21,24,[26][27][28][29][31][32][33][34]36,39 . In six studies, CMA was performed after a normal karyotype or QF-PCR result, in seven studies it was performed concurrently to karyotyping, and in the remaining 10 as a first-tier technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the fetal tissues are already well formed and visible, a fragment of the umbilical cord may be used for examination purposes. Miscarried material may also be analyzed in paraffin blocks [31]; such examinations may be carried out several years after the block is prepared [32].…”
Section: Assessment Of the Miscarried Materialsmentioning
confidence: 99%